ARTIFICIAL INTELLIGENCE IN HAJJ GUIDANCE: TECHNOLOGY-BASED LEARNING, ADAPTIVE AND IMMERSIVE LEARNING INNOVATION - Abdul Hafiz; Rasya Ahmad Nizar; Leli Romdaniah (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2025)
This article examines the use of Artificial Intelligence (AI) in Hajj guidance as a technology-based learning innovation. The background of this research is the need to improve the effectiveness and efficiency of the Hajj guidance process, which has been carried out conventionally. The research uses a descriptive-qualitative approach using literature studies and interviews with educational technology practitioners and Hajj guidance instructors. The results indicate that AI can be used to present interactive simulations, a Hajj fiqh Q&A chatbot, an automated assessment system, and personalized material based on pilgrim profiles. The use of this technology has the potential to improve pilgrims' understanding of the Hajj ritual while enriching the learning experience with a more adaptive and inclusive approach. This article recommends the development of a Sharia-based AI platform as part of the digital transformation of Hajj administration.